Paperworks : Contemporary works on paper by British Columbia artists. - Bennett, W.R.; Graham, Colin; Province of British Columbia (Victoria : Art Gallery of Greater Victoria, 1978)
Babcock, Stewart ; Bates, Maxwell Bennett ; Bates, Pat Martin ; Bell, Alistair ; Bowden, Gary ; Dobereiner, Wendy ; Eastcott, Wayne ; Evermon, Robert ; Featherston, William ; Fisher, Brian ; Grauer, Sherry ; Harvey, Donald ; Howarth, Glenn ; Jarvis, Donald ; Jorgensen, Fleming ; Kipling, Ann ; Lee-Nova, Gary ; Michener, Robert ; Morris, Michael ; Onley, Toni ; Pavelic, Myfanwy Spencer ; Piddington, Helen ; Ronald), Bill Reid (William ; Shadbolt, Jack ; Simpson, Gregg ; Sinats, Andrejs ; Smith, Gordon A. ; Steele, Bob ; Tait, Sylvia ; Tiessen, George ; Travers-Smith, Brian ; Williams, Judith ; Wise, Jack ; Wood, Allan ; Young, Robert
biografie
Engels & Frans
boek
Keywords: British Columbia